SERIES: ECONOMICS APPLIED TO PROCESS ENGINEERING (Part 2) COST VARIABILITY ANALYSIS COST-VOLUME-PROFIT - Porlles Loarte, José (2004)
In this second part is proposed to revise and to consolidate binding concepts in the models and analysis techniques cost-volume-utilities (C-V-U) that are pertinent in a vulnerable and very sensitive economy to the changes of the competitive forces. Furthermore it concepts of leverage operating and elasticity price of the demand so that the engineer of processes has more extensive criteria for his analysis and proposals of solutions with greater professional rigorousness.